Changes in morphological variability of shallot ( Allium ascalonicum L. ) due to colchicine and gamma irradiation - Sri Yunita Simanjuntak; Diana Sofia Hanafiah; Rosmayati Rosmayati (Universitas Sumatera Utara, 2018)
This research aims to see changes in morphology variability of shallot(Allium ascalonicum L.) due to colchicine and gamma irradiation. This research was conducted at the Faculty of Agriculture University of Sumatera Utara, Medan with the altitude of 32 m above sea level from april to june 2017. This research used plant material of shallot bulb from Marlumba accession. The data were analyzed using t-analysis. Percentage of germination, plant length, number of leaves, number of tillers, bulb diameter, wet bulb weight, dry bulb weight and number of chromosomes. The results showed the treatment of colchicine 6 ppm and 6 gray gamma irradiation effect the changes parameters of plant length, number of leaves, number of tillers, bulb diameter, wet bulb weight, dry bulb weight and number of chromosomes. 6 ppm colchicine treatment showed increasing plant productivity, increase the average length of plant, the number of leaves, number of tillers, bulb diameter, wet bulb weight, dry bulb weight and number of chromosomes. 6 gray gamma irradiation treatment resulted decreasing in plant productivity, lowering plant length, number of leaves, bulb diameter, number of tillers, bulb diameter, wet bulb weight and dry bulb weight.